Flexible one-dimensional Zn-based electrochemical energy storage devices: recent progress and future perspectives. Issue 47 (24th November 2021) - Zhai, Shengli; Jiang, Zhuosheng; Chen, Xuncai; Hui, Kwun Nam; Chen, Fuming
Abstract : This review article summarizes the development of one-dimensional Zn-based electrochemical energy storage devices. The existing obstacles are diagnosed, corresponding solutions are proposed, and future research directions are indicated accordingly. Abstract : One-dimensional (1D) Zn-based electrochemical energy storage devices (1DZESDs) have stood out in recent years as a promising candidate to power wearable electronics due to their unique features, such as good energy storage performance, high safety, low cost, environment friendliness, and mechanical flexibility. In the past few years, great progress has been made in exploring different 1DZESDs including Zn-ion batteries, alkaline Zn batteries, Zn–air batteries, and Zn-ion capacitors. Numerous strategies have been reported to improve their energy storage performance and mechanical properties, and even endow them with multifunctionality to meet the requirements of practical utilization. Here, we present a brief history of the development of 1DZESDs. Fundamental chemistry and significant achievements regarding different types of 1DZESD are highlighted. At the same time, we have critically examined current challenges and analyzed potential solutions for the fabrication and utilization of high-performance 1DZESDs. Beyond that, insightful perspectives on future efforts are provided to further push 1DZESDs towards practical utilization. The development of 1DZESDs is summarized here, with existing obstacles diagnosed, corresponding solutions proposed, and future directions indicated accordingly. We hope that this review will stimulate more research to realize the practical applications of 1DZESDs in powering wearable electronics.